2018
DOI: 10.1002/adma.201801891
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Standing 2D Hexagonal Aluminum Nitride Dielectric Crystals for High‐Performance Organic Field‐Effect Transistors

Abstract: The existence of defects and traps in a transistor plays an adverse role on efficient charge transport. In response to this challenge, extensive research has been conducted on semiconductor crystalline materials in the past decades. However, the development of dielectric crystals for transistors is still in its infancy due to the lack of appropriate dielectric crystalline materials and, most importantly, the crystal morphology required by the gate dielectric layer, which is also crucial for the construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The morphological and microstructural requirements for TFT dielectric layers are even more stringent than for semiconducting layers, to ensure low leakage currents, high breakdown voltages, high capacitances, and minimal bulk/interface trap densities. Thus, harsh processing conditions (>450°C/1 h) and/or significant film thicknesses (≥100 nm) are typically required for high-performance solutionprocessed MO dielectric films (10,39,(41)(42)(43). Here, we show that the present processing method yields high-quality Al 2 O 3 dielectric films for low-voltage MO TFT operation.…”
Section: Resultsmentioning
confidence: 62%
“…The morphological and microstructural requirements for TFT dielectric layers are even more stringent than for semiconducting layers, to ensure low leakage currents, high breakdown voltages, high capacitances, and minimal bulk/interface trap densities. Thus, harsh processing conditions (>450°C/1 h) and/or significant film thicknesses (≥100 nm) are typically required for high-performance solutionprocessed MO dielectric films (10,39,(41)(42)(43). Here, we show that the present processing method yields high-quality Al 2 O 3 dielectric films for low-voltage MO TFT operation.…”
Section: Resultsmentioning
confidence: 62%
“…By incorporating [6,6]-phenyl-C 61 -butyric acid methyl ester into polyimide (PI), an interfacial charge storage layer is formed between pentacene and the PI, which guarantees efficient carrier programming and lowvoltage operation. Furthermore, appropriate dielectric crystals, such as AlN 51 shown in Figure 3E,F, can decrease the prevalence of defects and charge traps in the channel, resulting in high-performance OFET devices with low-voltage operation. Most recently, a bilayer-type dielectric configuration, 52 in which the low-k polymer is modified on a high-k fluoropolymer as a buffer layer, has been employed (Figure 3G).…”
Section: Ofets-based Biosensorsmentioning
confidence: 99%
“…E, Device structure diagram based on AlN and DPA crystals. Reproduced with permission from Reference 51. Copyright 2018, John Wiley and Sons.…”
Section: The Overview Of Otfts‐based Biosensorsmentioning
confidence: 99%
“…However, AlN single-crystals have not yet been reported as a gate dielectric due to the lack of an ideal 2D morphology that combines a thin thickness and a large lateral dimension. Yang et al (2018) reported a 2D AlN crystal fabricated by a physical vapor transport method for the first time. The lateral dimensions of the 2D AlN range from hundreds of microns to a few millimeters, with a thickness between 200 and 400 nm.…”
Section: Ofets Based On Osc/2d Hybrid Structures Osc/2d Hybrid Fets Wmentioning
confidence: 99%
“…One typical approach is directly thermal evaporating organic molecules from a evaporator to the 2D materials which are placed in a sample holder above the evaporator (Wang and Hersam, 2009;Dou et al, 2011;Emery et al, 2011;Mao et al, 2011;Lemaitre et al, 2012;Singha Roy et al, 2012;Kim et al, 2015a,b;Nguyen et al, 2015Nguyen et al, , 2020Zheng et al, 2016). Another technique is physical vapor transport, that is when the organic powder is placed in a vacuum tube where the substrate with the 2D materials is placed in the same tube with a distance of several inches away from the organic powder, during which carrier gas can be employed or not (He et al, 2014;Lee et al, 2014Lee et al, , 2017Yang et al, 2018). For both methods, one common issue is that the organic semiconductor with a large conjugated unit tends to adopt face-on orientation initially, which usually is not favorable for common OFET transport.…”
Section: Introductionmentioning
confidence: 99%